Representations of Social Ideologies and Stereotypes in Selected English Nursery Rhymes - Olayemi, Oluwakemi Titilola (NIU Journal of Humanities, 2020)
Nursery rhymes have been found to be a very important part of learning at the nursery and primary school levels of education in Nigeria. Pupils are exposed to these poems as part of the means of impacting to them, the ability to appreciate reading and rhythm. This study highlights some English nursery rhymes with the aim of identifying their ideological imports and the possible meanings they convey to pupils. Excerpts from the lyrics of randomly selected nursery rhymes served as data. These were analysed based on Halliday’s (1985) systemic functional theory and. Fairclough’s (1993) Critical Discourse Analysis Approach which explores the relationship between texts and wider socio-cultural processes. Findings revealed that some English nursery rhymes denigrate motherhood, promote wickedness and covetousness in the boy-child, and present the girl child as frail and without a voice. These forms of representation and positioning of people have implications for the appreciation of social and moral values on the part of the children who are made to read and memorise the rhymes. If societies must produce civil members of their communities, care must be taken to censor what is being fed to children in their formative years. Keywords: Critical Discourse Analysis, Formative Years, Ideological Imports, Nursery Rhymes, Socio-Cultural Processes,